CUSTOMER SATISFACTION ANALYSIS OF LABORATORY SERVICE QUALITY WITH IMPORTANCE PERFORMANCE ANALYSIS METHOD IN UPTD. ABIANSEMAL PUSKESMAS I - Agus Ferry Sutrisna (Meditory : The Journal of Medical Laboratory, 2022)
Measuring the level of patient satisfaction is absolutely necessary in an effort to improve the quality of health services. Through these measurements, it can be seen to what extent the dimensions of the quality of health services that have been implemented can meet patient expectations. The existence of complaints from consumers regarding laboratory services can result in a decrease in consumer confidence to use laboratory services. The UPTD Laboratory of the Abiansemal I Public health center is required to always maintain consumer confidence by improving the quality of service so that customer satisfaction increases. The purpose of this study was to determine the level of conformity between expectations and reality received by patients  at the UPTD Laboratory of the Abiansemal I Public health center in 2022 and to find out which services should be a priority for improvement for improving the quality of laboratory services. This research is a non-experimental research with an exploratory qualitative research design using questionnaires and in-depth interviews. The study was conducted in January 2022 by taking samples of outside patients, aged 17-60 years. The level of satisfaction of outpatients with services at the UPTD Clinical Laboratory of the Abiansemal I Public health center is quite high, however, there are services that have not been carried out properly and optimally so that they have not provided satisfaction to laboratory customers.